Best practice in primary care pathology: review 4 - Smellie, W S A (BMJ Group, 2006)
This fourth best practice review examines four series of common primary care questions in laboratory medicine are examined in this review: (1) safety monitoring for three common drugs; (2) use of prostate‐specific antigen; (3) investigation of vaginal discharge; and (4) investigation of subfertility. The review is presented in question–answer format, referenced for each question series. The recommendations represent a precis of the guidance found using a standardised literature search of national and international guidance notes, consensus statements, health policy documents and evidence‐based medicine reviews, supplemented by Medline Embase searches to identify relevant primary research documents. They are not standards but form a guide to be set in the clinical context. Most of them are consensus based rather than evidence based. They will be updated periodically to take account of new information.